Financing Fund for Access to the Higher Education System - Márquez-Chaves, Carlos Augusto; Pruneda-Ávila, Nancy Elizabeth; Zúñiga, Juan Manuel Martínez; Gallegos-Gonzales, Orlando; Ubilla-Briones, Edith Carola; Godoy-Cerda, Johanna Solange; Casanueva-Yáñez, Galvarino; Rengifo-Lozano, Raúl (Journal of Ecohumanism, 2024)
This document aims to study some of the financing strategies that promote access to the public higher education system in Colombia. It seeks to build the path of public policy recommendations, a forgivable financing scheme aimed at citizens of strata 1, 2 and 3 to access the official higher education system in the municipality of Soacha in Colombia. To achieve the above, the study proposes a non-experimental method, which stands out for using documentary research techniques for observation and a documentary analysis technique for educational public policy. In this sense, the strategy is framed in content analysis and has an eminently qualitative component. Under this method, it is possible to conclude that it is an economic, political and especially cultural challenge, access to higher education, which must be considered within the framework of equity and equality of social justice, leaving aside the government policies that generally vary in the shift of government resulting in dependence on personal volunteers. As a result, the fund administration funds guarantee the improvement of educational quality in terms of access and coverage. For the latter, they commit subsidized strategies where the favored students project their research initiatives in the territorial development of the regions from which they come.